Vasodilator Activity of Compounds Isolated from Plants Used in Mexican Traditional Medicine - Luna Vázquez, Francisco; Ibarra Alvarado, César; Camacho Corona, María del Rayo; Rojas Molina, Alejandra; Rojas Molina, J.; García, Abraham; Bah, Moustapha (2018)
Abstract: Arterial hypertension is one of the main risk factors in the development of cardiovascular diseases. Therefore, it is important to look for new drugs to treat hypertension. In this study, we carried out the screening of 19 compounds (triterpenes, diterpenes, sesquiterpenes, lignans, and ﬂavonoids) isolated from 10 plants used in Mexican traditional medicine to determine whether they elicited vascular smooth muscle relaxation and, therefore, could represent novel anti-hypertension drug candidates. The vasorelaxant activity of these compounds was evaluated on the isolated rat aorta assay and the results obtained from this evaluation showed that three compounds induced a signiﬁcant vasodilatory effect: meso-dihydroguaiaretic acid [half maximal effective concentration (EC50), 49.9 ± 11.2 µM; maximum effect (Emax), 99.8 ± 2.7%]; corosolic acid (EC50, 108.9 ± 6.7 µM; Emax, 96.4 ± 4.2%); and 5,8,40-trihydroxy-3,7-dimethoxyﬂavone (EC50, 122.3 ± 7.6 µM; Emax, 99.5 ± 5.4%). Subsequently, involvement of the NO/cyclic guanosine monophosphate (cGMP) and H2S/ATP-sensitive potassium channel (KATP) pathways on the vasodilator activity of these compounds was assessed. The results derived from this analysis showed that the activation of both pathways contributes to the vasorelaxant effect of corosolic acid. On the other hand, the vasodilator effect of meso-dihydroguaiaretic acid and 5,8,40-trihydroxy-3,7-dimethoxyﬂavone, partly involves stimulation of the NO/cGMP pathway. However, these compounds also showed an important endothelium-independent vasorelaxant effect, whose mechanism of action remains to be clariﬁed. This study indicates that meso-dihydroguaiaretic acid,corosolicacid,and5,8,40-trihydroxy-3,7-dimethoxyﬂavonecouldbeusedasleadcompoundsfor the synthesis of new derivatives with a higher potency to be developed as drugs for the prevention and treatment of cardiovascular diseases. Keywords: corosolic acid; 5,8,40-trihydroxy-3,7-dimethoxyﬂavone; meso-dihydroguaiaretic acid hydrogen sulﬁde; nitric oxide; vasorelaxation